A Comparison of Anti-inflammatory Activity of Ethanol Extracts of Young and Old Areca Seeds (Areca catechu L.) in vitro - Legasari, Leni; Wati, Ambar; Yani, Dwi Fitri (Department of Chemistry - Universitas Bangka Belitung, 2023)
Areca catechu L. has been widely used as a traditional medicine in medicinal practices in various countries around the world. Areca nut contains secondary metabolite compounds such as alkaloids, flavonoids, triterpenoids, steroids, and tannins so it has great potential to be developed as a medicine. The use of anti-inflammatory drugs from natural ingredients is widely developed because synthetic non-steroidal anti-inflammatory drugs cause side effects to the body such as nausea, diarrhea, headaches, and stomach ulcers. This study aims to determine the content of secondary metabolites and determine the anti-inflammatory activity of ethanol extracts of young and old areca nut seeds. Old areca nut seeds used are areca nut fruits that have an orange color while young areca nut seeds are areca nut fruits that have a green color. The anti-inflammatory activity test method was carried out using the protein denaturation inhibition method at 5, 10, 15, and 20 ppm extract concentrations. The results of this study indicate that young and old areca nut seeds positively contain alkaloids, flavonoids, tannins, and saponins and negatively contain steroids. The results of anti-inflammatory activity testing show that ethanol extracts of young and old areca nut seeds have the potential as anti-inflammatory because they have a percentage value of protein denaturation inhibition greater than 20%. A comparison of anti-inflammatory activity between areca nut seeds can be seen from the IC50 value of ethanol extract. The IC50 results show that young areca seeds have an IC50 value of 7.42 ppm which is higher than the old areca seeds of 11.52 ppm